SEMIOTICS DECONSTRUCTIVE STUDY TOWARDS ARABIC LOANWORDS ON JIHAD IN THE BOOK AKU MELAWAN TERORIS - Kamil, Sukron; Hidayati, Sri (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2021)
Although terrorism belongs to many ideologies and religions in the world, now, terrorism in the name of Islam has swept across many regions of the world, from East to West, and has also been widely studied. However, studies on its relationship with Arabic language are lacking or even non-existent. Therefore, this article bases its exploration on a literature review methodology with a semiotic structuralism theory approach. This research found that based on Imam Samudra's book, JI/NII terrorist circles use Arabic loanword far more than mainstream moderate Islam, especially in social issues. This shows that the more Arabic loanwords, especially in Islamic socio-political texts, the more fundamentalist they are. In Imam Samudra's book, a number of Arabic words were also found which were given new connotations of a jihadist/terrorist fundamentalist nature. In addition, Imam Samudra's understanding of many Arabic loanwords such as jihad fi sabilillah (jihad in the way of Allah) is also wrong because it is not based on the context of the text and its social context as well as a standard methodology of interpretation in Islam. His jihad understanding cannot be accounted for in Islamic science and language.